Impact of CiteGuru Mobile Application on Referencing Competency - Mohamad Rahimi Mohamad Rosman; Nik Nur Izzati Nik Rosli; Amira Idayu Mohd Shukry; Noor Masliana Razlan; Noor Azreen Alimin; Nurfatihah S Baharuddin; Noor Rahmawati Alias (Malaysia Journal of Invention and Innovation, 2022)
Reference competency is the ability, skills, and knowledge to properly write, interpret, and communicate referencing styles and standards. Reference competency is an important predictor of individual impacts such as performance satisfaction, and net benefits. Thus, CiteGuru mobile application was developed as an effort to improve the ability, skills, and knowledge of an individual in relation to referencing competency. The mobile application was developed based on Android Studio 3.1.17 and released to Google Play Store. However, since its inception, the impact of the application has never been investigated. Therefore, the purpose of this study is to investigate the impact of the CiteGuru application on its stakeholders.